Innovation and new product planning - Kahn, Kenneth B.; Mohan, Mayoor (New York, NY : Routledge, 2021)
"This practical text introduces readers to the essential business aspects of innovation and new product planning. The product planning process is discussed across two broad themes: product development and product management. Importantly, the book emphasizes the 21st-century strategic and creative mindset necessary to drive businesses' innovation activities in a concise, yet comprehensive manner. The book delves into the front-end of innovation and formal product development activities, examining the topics of opportunity identification, concept generation and evaluation, technical development, product design, testing, launch strategies, product management, life-cycle management, brand management, and vital elements for international success. There are standalone notes that serve to apprise readers on related topics such as the use of agile product development methodologies, the formation of business entities, and recommended best practices for new product development. The book excels at providing relevant examples and applied tools that augment the concepts to offer valuable connections to real-world product planning efforts. This text is particularly useful as a guide to learning the fundamental concepts and strategies associated with innovation and new product planning. Among student audiences, upper-level undergraduate and first-year graduate students are likely to benefit as the book embraces its position to serve as a primer on product development and management"--
OCLC-licensed vendor bibliographic record.
Keywords: New products; Product management; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Entrepreneurship